PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS INFORMASI DENGAN SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL MODERASI - Purnama Ramadhan; Rudy Fachruddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This research is aimed to verify the influence of the influence of organizational culture on the quality of information with the accounting information system as a moderation variable, survey on conventional banks in Banda aceh, Bank Mandiri, BNI ( Bank Negara Indonesia ) , BRI ( Bank Rakyat Indonesia) , and BTPN (Bank Tabungan Pensiunan Negara)and Bank BCA(Bank Central Asia). The population in this study are the users of the system at these banks were selected at random. There are randomly selected 50 people. The collecting of data and information needed  in this research was done  by field research.The data used  is primary data collected directly from the subject of research by a questionnaire form. The testing of the influences of independent variables toward  dependent variable with moderation variable as moderator was  done by using multiple regressions model. The results showed that organizational culture has a significant effect on the quality of information. Accounting information system is not a moderating variable between the influence of organizational culture on the quality of information. The results of this study suggest that conventional banking in Banda Aceh should be able to improve the quality of information by running the function of the accounting information system so that the quality of information will be better.